Cassava Peels Processing - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Cassava Peels processing describes the opportunity for additional income in turning waste to wealth, An innovation that feeds sector individuals, business people and private sector can explore for profitability.